Eco-clusters as driving force for greening regional economic policy - Alina Pohl (WWWforEurope, 2015)
This research investigates eco-clusters as driver for greening regional economic policy and examines necessary incentive structures to foster eco-innovation as well as growth and employment in the eco-industry sector. Eco-clusters are seen in context with sustainability and environmental friendly behavior as means for a socio-ecological transition in the long run. The main hypothesis implies that eco-clusters have to be policy driven and established top-down and therefore differ from cluster structures in other industries. Possible reasons are uncertainty on a developing market as well as external effects of eco-innovations; the latter are seen as radical innovations. Based on theoretic findings for the establishment of clusters and general research findings for eco-clusters and eco-innovations, it is differentiated between a spontaneous cluster emergence from private initiatives through self-reinforcing forces of companies in a region (bottom-up), and the formation of a policy-driven network with primarily regional objectives to stimulate the competitive advantage of the regional industrial location (top-down). The hypothesis will be proofed by empirical results gained through personal interviews and complemented by findings in current research literature. Finally, implications for incentive structures to green economic policy are identified. It is shown that eco-clusters are different to other clusters and crucial for a long-term sustainable change and thus need political commitment and public incentives. For empirical observation, eco-clusters in Austria were selected. This research relates to the ongoing debate on green growth and develops policy incentives for establishment of eco-clusters and thus greening of economic policy.
Keywords: C38; I31; O31; O44; Q01; Q55; Q58; 330; Cluster Analysis; Ecological Cluster; Ecological Innovations; Regional Economic Policy; top-down vs. bottom-up